2022
DOI: 10.3390/bios12121104
|View full text |Cite
|
Sign up to set email alerts
|

Ir(III) Complexes with AIE Characteristics for Biological Applications

Abstract: Both biological process detection and disease diagnosis on the basis of luminescence technology can provide comprehensive insights into the mechanisms of life and disease pathogenesis and also accurately guide therapeutics. As a family of prominent luminescent materials, Ir(III) complexes with aggregation-induced emission (AIE) tendency have been recently explored at a tremendous pace for biological applications, by virtue of their various distinct advantages, such as great stability in biological media, excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 85 publications
(108 reference statements)
0
13
0
Order By: Relevance
“…Transition metal complexes have emerged as promising therapeutic tools in photopharmacology due to several unique properties, including a wide range of coordination numbers, oxidation states, and geometries. , Among transition metals, Pt­(IV), Ru­(II), Rh­(III), Ir­(III), and Os­(II) are very attractive candidates for PDT applications since they tend to absorb in the visible region of the electromagnetic spectrum and exhibit relatively high photostability and long luminescence lifetimes (>100 ns), being an interesting alternative to PSs based on organic fluorophores on clinical use such as porphyrins or chlorins. In this context, cyclometalated iridium­(III) complexes show excellent anticancer activities and a great potential to overcome some of the main drawbacks of conventional platinum-based chemotherapy (i.e., resistance and toxic side effects). , Such metal complexes are likely good candidates for PDT applications as they combine appealing photophysical and photochemical properties within a single compound, including large Stokes’ shifts, high luminescent quantum yield, and high efficient singlet oxygen production upon light irradiation. Photosensitizers based on cyclometalated Ir­(III) complexes have been used also as photocatalysts in systems for photocatalytic hydrogen evolution reactions. , However, most reported cyclometalated iridium­(III) complexes are quite cytotoxic in the dark and only activatable with short wavelengths of light, which compromises further development of efficient PDT agents.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal complexes have emerged as promising therapeutic tools in photopharmacology due to several unique properties, including a wide range of coordination numbers, oxidation states, and geometries. , Among transition metals, Pt­(IV), Ru­(II), Rh­(III), Ir­(III), and Os­(II) are very attractive candidates for PDT applications since they tend to absorb in the visible region of the electromagnetic spectrum and exhibit relatively high photostability and long luminescence lifetimes (>100 ns), being an interesting alternative to PSs based on organic fluorophores on clinical use such as porphyrins or chlorins. In this context, cyclometalated iridium­(III) complexes show excellent anticancer activities and a great potential to overcome some of the main drawbacks of conventional platinum-based chemotherapy (i.e., resistance and toxic side effects). , Such metal complexes are likely good candidates for PDT applications as they combine appealing photophysical and photochemical properties within a single compound, including large Stokes’ shifts, high luminescent quantum yield, and high efficient singlet oxygen production upon light irradiation. Photosensitizers based on cyclometalated Ir­(III) complexes have been used also as photocatalysts in systems for photocatalytic hydrogen evolution reactions. , However, most reported cyclometalated iridium­(III) complexes are quite cytotoxic in the dark and only activatable with short wavelengths of light, which compromises further development of efficient PDT agents.…”
Section: Introductionmentioning
confidence: 99%
“…LPS or LTA) and the selective discrimination, imaging, and elimination of Gram-negative and Gram-positive pathogenic bacteria due to their various advantages such as kinetic inertness, positive charge, tunable photophysical and photochemical properties, generation of high levels of reactive oxygen species, the ease of synthesis, etc . 39–43…”
Section: Introductionmentioning
confidence: 99%
“…which make them excellent candidates for applications in organic light-emitting diodes, biosensing, bioimaging and therapy. 2,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] These AIEgen metal complexes can interact with bacteria or their pathogenic components through various noncovalent modes such as electrostatic interactions, hydrogen bonds, van der Waals forces and hydrophobic interactions. 2 For example, Ding and Yu's groups have developed an AIE-active cationic Pt(II) complex [Pt(N^N^N)Cl] + , where N^N^N is 2,6-bis(benzimidazol-2′-yl)pyridine with hexaethylene glycol methyl ether groups, which demonstrated sensing of LPS and rapid wash-free discrimination of Gram-negative and Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high emission quantum efficiency, colorful emission properties, high stability and low cytotoxicity, iridium­(III) complexes are widely used in electroluminescence, sensing, AIE and dye-sensitized solar cells. A series of metal iridium­(III) complexes with AIE activity were synthesized by using ĈN-type bidentate ligands as cyclometaled ligands and triazole pyridine derivatives as auxiliary ligands by Su’s group, and it showed that AIE activity mainly came from the charge transfer intraligand ( 3 ILCT) excited state . A kind of binuclear iridium­(III) Shiff base complexes were developed by Bryce’s group, and it was found that there were some interactions between benzene rings, which made the geometric structure more planar, and activated AIE phenomenon .…”
Section: Introductionmentioning
confidence: 99%